NEUROCARDIOGENIC SYNCOPE AND EXTRACURRICULAR ACTIVITIES OF ADOLESCENTS IN THE HIGH-INTENSITY EDUCATIONAL PROCESS - A. V. Pogodina; V. V. Dolgikh; А. N. Rodionova; L. V. Rychkova; О. V. Valyavskaya ("Paediatrician" Publishers LLC, 2014)
Background: Neurocardiogenic syncope (NCS) is widespread among adolescents, which makes it relevant to study the factors contributing to the implementation of syncopic readiness in susceptible persons. Objective: The aim was to assess the connection between extracurricular activities of adolescents and the emergence of NCS. Methods:The questionnaire survey among the Lyceum students aged 14-18 tried to find out the presence of syncope (presyncope) and its nature in a child's medical history; the nature and intensity of extracurricular loads; and intensity and success of curricular activities. Results: The study included the results of the questionnaire survey among 286 students (62.2% girls). Syncope and presinkope states were observed in a medical history of 136 (47.6%) students, and 105 (77%) of them had NCS. Independent risk factors for the development of NCS were private lessons with tutors, and only in cases where a child had no other extracurricular classes (creative, sports) - OR 6.4 (95% CI 1.7-24.8). The NCS risk was also higher in adolescents, who had good grades at school - OR 2.2 (95% CI 1.1-4.6). Conclusion: The risk of NCS development in teenage schoolchildren is defined by the area of subject education: high risk of this kind of syncope is in children, who have private classes with tutors and no other extracurricular loads, as well as in children, who have good grades at school.